Analysis of Landslide Handling With Mini Pile Reinforcement Using Plaxis Software on The “X” Toll Road Project - Rumbyarso, Yonas Prima Arga; Pribadi, Gali (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The Semarang-Demak Toll Road faces geotechnical problems due to geological conditions that include hilly areas and basins, with bedrock such as claystone, shale, and lignite that are prone to weakening. A landslide occurred at the Semarang-Demak Toll Road site between Sta. 1+250 and Sta. 2+715, despite various methods of embankment work that were not entirely successful, therefore causing damage. The analysis showed a discrepancy between the theoretical factor of safety and the actual landslide condition, requiring slope reinforcement technology such as mini piles that effectively inhibit soil movement. Mini piles, in the form of reinforced concrete with a length of 7 to 10 meters and a spacing of 2 meters between piles, plus the use of geotextiles, analyzed using the Plaxis 2D program showed an increase in the factor of safety. Although there were slight differences between the reinforcement models, the combination of mini piles and geotextiles proved effective, especially when placed in hard soil layers or over soft soil at a depth of 7 meters from the surface, overcoming the embankment loads at the site.